The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1080/02602938.2016.1195333
|View full text |Cite
|
Sign up to set email alerts
|

Clarity, consistency and communication: using enhanced dialogue to create a course-based feedback strategy

Abstract: . Telephone: 0151 2312805.Clarity, consistency and communication: using enhanced dialogue to create a coursebased feedback strategy.This article examines the outcomes of a study across four discipline areas in order to develop course-based assessment strategies in closer co-operation with students. Second year students (n=48) from different disciplines were engaged in two phases of activity-orientated workshops. Phase one sought their perceptions of feedback. Phase two saw students design a proposed strategy t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 33 publications
(36 reference statements)
0
7
0
Order By: Relevance
“…The staff were sent the students' ideas about their course-level feedback prior to the co-creation workshop. They then met with the students and, between them, they created the programme feedback strategy (see Nixon et al, 2016). The overall process resulted in a programme-level feedback strategy for each of the four programmes, written by staff and students.…”
Section: About This Studymentioning
confidence: 99%
“…The staff were sent the students' ideas about their course-level feedback prior to the co-creation workshop. They then met with the students and, between them, they created the programme feedback strategy (see Nixon et al, 2016). The overall process resulted in a programme-level feedback strategy for each of the four programmes, written by staff and students.…”
Section: About This Studymentioning
confidence: 99%
“…Jonsson, 2012;Li & De Luca, 2014). One solution that has been put forward is the introduction of audio, rather than written, feedback (Lunt & Curran, 2010), but to take effect this would need to be an accepted and approved practice in circumstances where time allocations for feedback may be written into institutional guidelines (Nixon, Brooman, Murphy, & Fearon, 2017). Thus the individual has limited capacity to enact change with regard to this category of constraint.…”
Section: Discussionmentioning
confidence: 99%
“…In association with this function much of the literature on this has included recommendations on how academics might amend their practices in order to achieve this (e.g. Nixon, et al, 2017;Rae & Cochrane, 2008;Robinson, Pope, & Holyoak, 2011;Williams & Smith, 2017a). There is, however, also a growing acknowledgement in the more recent literature in this area that there is more than one group of stakeholders in the feedback process whose needs should be taken into account.…”
Section: Discussionmentioning
confidence: 99%
“…Particularly important is the ability of students to understand the nature and purpose of university assessment tasks (Blair, 2017;Nixon et al, 2017). Nixon et al (2017) found that a large number of students tended to perceive themselves as recipients of feedback instead of active learners in it, and therefore, they were less proactive in taking the initiative in utilizing the feedback they received for further improvements. Such studies highlight the need for teachers and institutions to ''provide more training to students to enhance their assessment and feedback literacy in order for students to appreciate the value of assessment and feedback activities'' (Sun et al, 2022;Zhou et al, 2020).…”
Section: Academic Competencementioning
confidence: 99%